Evaluation and Redesign of Telkom University’s Open Library Website Interface Using the Goal Directed Design (GDD) Method - Zian Alfaen; Indra Lukmana Sardi; Monterico Adrian (Building of Informatics, Technology and Science (BITS), 2022)
As a university with World Class University quality, Telkom University provides information services with a website as the main source of libraries for its students. The website is called Open Library which provides information on all library collections owned by Telkom University which are open and can be loaned. One of the missions of this website is "To play an active role in increasing interest in reading and writing in the community". Because, a good digital library website is a library website that can increase the reading interest of users. Interface design is one of the most important elements to support the quality of digital libraries. Therefore, this study aims to evaluate the design and provide design solutions for the interface of the Open Library website. . The final evaluation used in this study used the System Usability Scale method. The System Usability Scale (SUS) is a measure of the usability of a product using a 10-question questionnaire developed by John Brooke. Of the 20 respondents who had filled out the questionnaire in the final evaluation, the result was 74.45. Where 74.45 is a score that has passed the average standard value of SUS